The Development of Supplementary Activities to Enhance Basic Recorder for Elementary Students Anubanlamplaimat School
The purposes of the research were to develop a set of supplementary activities to enhance basic recorder, evaluate the quality level of the activity set, and study students’ satisfaction with the activity set. The sample was selected through purposive sampling, using the classroom as the unit of randomization, specifically 34 students from Grade 5/1 at Anubanlamplaimat School. The research instruments included a set of activities to enhance basic recorder, an activity quality assessment form, a skills assessment form, and a satisfaction questionnaire regarding the activities. Data analysis was conducted using Mean, percentage, standard deviation The research results were found: The development of supplementary activities to enhance basic recorder for elementary Students Anubanlamplaimat School. The researcher had been developed with set of 8 basic recorder blowing skill enhancement activities for elementary school students at Anubanlamplaimat School. The quality was appropriate, with an IOC of 0.68, which higher than the specified threshold, making it suitable for using with the sample group. The quality level of the activity set evaluated by experts was at the highest level, at 4.68. The score before using the activity set was 10.85, and the score after using the activity set was 16.58. The comparison between the scores before and after using the activity set for the same group of students was 32.65. Satisfaction with the activity set was at the highest level of satisfaction ( = 4.68, S.D. = 0.46